New Student Pesantren Program as an Instrument for Enhancing Fiqh Worship Literacy among Islamic University Students - Parihat; Muhammad Fauzi Arif; Ahmad Mujahid Rasyid; Shindu Irwansyah; Fahmi Fatwa Rosyadi Satria Hamdani (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2025)
Islamic higher education institutions play a strategic role in shaping students' religious understanding, particularly in the area of fiqh worship practices. This foundational aspect of Islamic studies is essential for cultivating a balanced and contextualized approach to religious life among students. The New Student Pesantren Program serves as an integrated religious orientation model aimed at strengthening students’ comprehension and practice of fiqh from the beginning of their academic journey. This study seeks to evaluate the effectiveness of the program in enhancing students’ understanding of fiqh worship within Islamic universities. A mixed-methods approach was adopted, incorporating both quantitative and qualitative data through surveys, comprehension tests, and case study observations. The research involved first-year students selected through purposive sampling. Key instruments included a structured questionnaire and a fiqh worship comprehension test. Data were analyzed using triangulation techniques to ensure the validity and reliability of findings. Results from the Wilcoxon Signed-Rank Test showed a significance value of 0.000, which is lower than the threshold of 0.05. This confirms a statistically significant improvement in students’ understanding of fiqh worship after participating in the program. Therefore, the New Student Pesantren Program is proven to be an effective initiative in improving fiqh worship literacy, contributing to the broader goal of religious development in Islamic higher education settings.